Loneliness in the workplace: feelings and expressivity of hotel employees - Bekir Bora Dedeoğlu; Caner Çalışkan; Tzu-Ling Chen; Jacek Borzyszkowski; Fevzi Okumus (International Hospitality Review)
Purpose – This study investigates the relationship between feelings of loneliness in the workplace, life satisfaction, affect, hope and expressivity among hotel employees. Design/methodology/approach – The research model was tested via structural equation modeling based on the empirical data collected from hotel employees in Antalya, Turkey. Findings – The research findings suggest that emotional deprivation and social companionship have a significant impact on life satisfaction, that life satisfaction has a significant impact on positive and negative emotions, and that positive and negative emotions have the same impact on pathways and agencies. Originality/value – The research findings should assist researchers and practitioners to understand the behaviors of hotel employees in continuous interaction and relationship with individuals to motivate them while providing more effective services.